Labor market flexibility and job security measures in a global economy: New challenges ahead - Marshall, Ray; Van Adams, Arvil (Estudios de Economía, 2016)
Measures assuring job security are sought by workers and their representatives to protect themselves against economic fluctuations and the loss of jobs and incomes. In sectors of an economy that require a skilled workforce employers are often willing to provide promises of job security in exchange for lower labor turnover to protect investments in the skills of their workers, facilitate internal flexibility, and improve labor relations. This contractual exchange serves the interest of both parties and when achieved in a market setting enhances economic behavior. Governments, on the other hand, are also interested in job security as an instrument of social policy to address market failures and equity concerns. Public interventions to stabilize employment can force firms to become more efficient by focusing adjustment on productivity instead of wages or they can threaten the efficient operation of labor markets by introducing uncertainty and raising labor costs.